2020
DOI: 10.3389/fmicb.2020.603578
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Diversity of CTX-M-Producing Escherichia coli From the Seine River

Abstract: CTX-M-producing Escherichia coli are spreading since 1999 both in clinical and in community settings. Environmental samples such as rivers have also been pointed out as being vectors for ESBL producers. In this report, we have investigated the presence and the diversity of CTX-M-producing E. coli isolates in two samplings of the Seine River (next to Notre Dame), Paris France, performed in June 2016 and 2017. The total number of bacteria growing on the selective ChromID ESBL agar was 3.1 × 105 cfu/L (23.8% of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…It is well-known that the overuse of antimicrobials in agriculture may lead to an increased selection of resistant strains [ 60 ]. However, it seems that one of the essential reasons for a high prevalence of antimicrobial resistance genes in the environment may be the horizontal transfer of these genes from fecal microbiota of livestock to environmental bacteria [ 61 , 62 ]. The tetW gene, the most widespread tetracycline resistance determinant in bacteria of different origins, may be a good example of disseminating resistance genes among clinical and environmental strains.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the overuse of antimicrobials in agriculture may lead to an increased selection of resistant strains [ 60 ]. However, it seems that one of the essential reasons for a high prevalence of antimicrobial resistance genes in the environment may be the horizontal transfer of these genes from fecal microbiota of livestock to environmental bacteria [ 61 , 62 ]. The tetW gene, the most widespread tetracycline resistance determinant in bacteria of different origins, may be a good example of disseminating resistance genes among clinical and environmental strains.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported the predominance of CTX-M ESBLs among environmental E. coli . For example, CTX-M-14(-like) was prevalent among ESBLEC in surface waters in China, Japan, and Korea, and CTX-M-15 was prevalent among ESBLEC in surface waters in France, Germany, and Switzerland ( Falgenhauer et al., 2021 ; Girlich et al., 2020 ; Jang et al., 2013 ; Liu et al., 2018 ; Miyagi and Hirai, 2019 ; Zurfluh et al., 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, some previous studies also detected ESBL genes on chromosomes and suggested that integration of ESBL genes into chromosomes could contribute to the maintenance of ESBL genes in the absence of antibiotic selection pressure (5)(6)(7). Although previous studies have reported the occurrence of ESBLEC in environmental waters, limited information exists regarding the locations (chromosome or plasmid) and genetic contexts of ESBL genes in environmental ESBLEC (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%